Generative AI as source of change of knowledge management paradigm - Kaczorowska-Spychalska, Dominika; Kotula, Nina; Mazurek, Grzegorz; Sułkowski, Łukasz (Human Technology, 2024)
The launch of ChatGPT in November 2022 revolutionized the accessibility of generative Artificial Intelligence, enabling conversational interactions. Extensively tested by millions, its influence on management has become a subject of debate. In the digital revolution, generative Artificial Intelligence possesses transformative potential, automates tasks, delivers novel goods and services, and generates valuable insights. However, challenges such as data quality, human oversight, and ethical considerations arise in the context of digital transformation. This research employs qualitative research methods to examine the current understanding of generative Artificial Intelligence and predict its influence on the knowledge management within organizations. By conducting a survey among industry experts, this paper aims to provide valuable insights into the integration of generative Artificial Intelligence and its implications for the knowledge management paradigm.